¬¬¬Design of search information system using mobile application for car problems in Deli Serdang regency - Matondang, Aprima; Simanjuntak, Andrean; Simanjuntak, Mutiara; Simangunsong, Juanto (Institute of Computer Science (IOCS), 2024)
We successfully developed the mobile program that can solve the car problems that may be difficult to find the location of garage service. We developed MyBengkel as the solution of the problems between car owners and garage location. We delve into the common types of car problems encountered by drivers and explore the methods used to diagnose and resolve them. From routine maintenance to complex repairs, we will discuss the underlying causes of these issues and examine the technologies and tools employed in modern automotive diagnostics. The location interest in Deli Serdang regency and ist surrounding. The data compilation shows the total casualties in 2021 and 2022 is ranging at 80 – 120 cases in Deli Serdang with various roads type. This application makes it easy to get information on car problems facilities, appropriate prices and boarding car and garage service locations for local peoples and increases promotional opportunities for the garage owners in Deli Serdang locations